The Relationship of Religiosity and Peer Conformity with Students’ Attitude toward Prosocial Behavior - Nur Hafiza; Neviyarni Neviyarni; Yarmis Syukur (International Conferences on Educational, Social Sciences and Technology)
The depletion of students’ prosocial behavior is one of the problems associated with how students’ religiosity level and how students conform to behavior of peers. The aims of this study were to reveal the relationship between religiosity, peer conformity with students’ attitude toward prosocial behavior. The method used was quantitative, descriptive correlational type. The population was 332 students and 62 students were taken as the sample by using proportional stratified random sampling technique. The instruments are religiosity scale (17 valid items, α=0,806), peer conformity scale (15 valid items, α=0, 732) and students’ attitude toward prosocial behavior scale (53 valid items, α=0,944). The data were analyzed by multiple regression. The result showed a correlation coefficient R = 0,638 and p = 0,000 (p < 0,05). That result indicated there is a positif and significant relationship between religiosity and peer conformity with students’ attitude toward prosocial behavior. The implication of this study could be used as need assessment to guidance and counseling services.